Ma’kombongan Based Group Investigation Learning Model In Analyzing Controversial Cases Related To The Teaching Of Civic Education - Roberto Salu Situru; Trivena Trivena; Resnita Dewi; Arnold Sule (Universitas Cokroaminoto Palopo, 2023)
Civic Education learning is considered boring by some students, mainly because the subject matter and delivery are presented in a one-way format. Civic Education in higher education should transition to a problem-based learning approach, making it more contextual and dynamic. Civic Education in college shouldn't be monotonous memorization; instead, it should focus on enhancing analytical and applicative thinking skills and the ability to provide input on existing phenomena or issues. Therefore, a learning model that encourages active student participation, such as the problem-based , is needed. This model aims to explore the depth of controversial issues discussed by students. The research results reveal the controversial issues and how the ma'kombongan-based group investigation process can improve students' analytical skills and reasoning abilities.